2017
DOI: 10.1051/e3sconf/20171901002
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of the electric energy production from photovoltaic conversion using mobile and fixed constructions

Abstract: Abstract. The paper presents the most representative -from the three-year measurement time periodcharacteristics of daily and monthly electricity production from a photovoltaic conversion using modules installed in a fixed and 2-axis tracking construction. Results are presented for selected summer, autumn, spring and winter days. Analyzed measuring stand is located on the roof of the Faculty of Electrical Engineering Poznan University of Technology building. The basic parameters of the statistical analysis lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Considering the available dataset and the type of variables Kruskal-Wallis test was applied. This nonparametric method is the extended version of the Mann-Whitney U test (Bugała et al, 2017). This statistic could identify whether the data comes from the same distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the available dataset and the type of variables Kruskal-Wallis test was applied. This nonparametric method is the extended version of the Mann-Whitney U test (Bugała et al, 2017). This statistic could identify whether the data comes from the same distribution.…”
Section: Methodsmentioning
confidence: 99%
“…2 it was found that, on a yearly basis, 1 kW of capacity installed in a PV system will generate 1,060 kWh, which results in a capacity factor of 12.1%. Such values are common for this part of Europe [9]. The way how residual load and selfconsumption were calculated are provided in section 3.1.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the document also includes the following provisions: the share of energy from renewable sources in the energy consumed in the EU is to be at least 27%. To this end, EU countries should establish common goals and implement them ambitiously [43,[54][55][56][57][58][59][60].…”
Section: Renewable Energy Sources and The Energy Policy Of The European Unionmentioning
confidence: 99%
“…Source: Own analyses based on data:[21][22][23][24][25][26][27][54][55][56][57][58][59][60][61][62]76].…”
mentioning
confidence: 99%